1993
DOI: 10.1038/eye.1993.73
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival bupivacaine in strabismus surgery

Abstract: A prospective study was performed to assess the effect of subconjunctival bupivacaine on pain relief following strabismus surgery. A total of 36 children were randomly allocated to receive either subconjunctival infiltration of bupivacaine or normal saline at the conclusion of surgery. Post-operative pain was evaluated using a 4-point assessment score. Subconjunctival bupivacaine provided significantly better post-operative pain relief (P < 0.001). We suggest that it could be used routinely in strabismus surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…10 Topical amethocaine 1% drops and subconjunctival infiltration with bupivacaine 0.5% administered at the conclusion of strabismus surgery have been shown to be equally effective in reducing postoperative pain, [11][12][13] although another study did not show any additional analgesic effect of either of these interventions when compared to placebo. 14 Our pilot study found that a subtenons injection of lidocaine was associated with a reduction in postoperative systemic analgesia requirement (29% vs. 64% of controls, P ϭ 0.052), and with a trend to reduced pain scores that reached statistical significance at the 2-h observation.…”
Section: Discussionmentioning
confidence: 97%
“…10 Topical amethocaine 1% drops and subconjunctival infiltration with bupivacaine 0.5% administered at the conclusion of strabismus surgery have been shown to be equally effective in reducing postoperative pain, [11][12][13] although another study did not show any additional analgesic effect of either of these interventions when compared to placebo. 14 Our pilot study found that a subtenons injection of lidocaine was associated with a reduction in postoperative systemic analgesia requirement (29% vs. 64% of controls, P ϭ 0.052), and with a trend to reduced pain scores that reached statistical significance at the 2-h observation.…”
Section: Discussionmentioning
confidence: 97%
“…Lignocaine is a shorter-acting anaesthetic with a duration of 1–2 h when given as a sub-Tenon block, while the effect of bupivacaine and levobupivacine lasts for 3–3.5 h 22. Similarly, the administration of postoperative subconjunctival bupivacaine has reduced pain scores after strabismus surgery in children 16. Another study compared subconjunctival bupivacaine to topical tetracaine in children having squint surgery, with both giving effective analgesia 17.…”
Section: Discussionmentioning
confidence: 99%
“…el‐Kasaby et al . (22) evaluated the effects of subconjunctival bupivacaine instillation along with preemptive oral acetaminophen and topical amethocaine in children undergoing ophthalmic surgery. Watson (23) and Habib (24) have evaluated topical amethocaine after strabismus surgery.…”
Section: Discussionmentioning
confidence: 99%